Empowering Scout Members of the 015-016 Scout Group through Digital Screen-Printing Training to Foster Creative Entrepreneurship in Dolok Ilir - Tulus; Nuraini Abdul Azis; Tulus Joseph Marpaung; Putri Khairiah Nasution; Suriati; J.L. Marpaung (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service program aimed to empower members of the 015-016 Scout Group at SMP Swasta Dolok Ilir, Indonesia, through digital screen-printing training to foster creative entrepreneurship. The program was implemented using a participatory and experiential learning approach, integrating digital graphic design training, hands-on practice with Direct-to-Film (DTF) screen-printing technology, product production, and basic entrepreneurial orientation. Training activities were supported by international collaboration with lecturers from Malaysia as part of strengthening Indonesia–Malaysia cooperation in education and community engagement. The results showed a clear improvement in participants’ digital skills, creativity, and practical production abilities. Most participants were able to independently design and produce screen-printed products with acceptable quality standards. The provision of modern screen-printing equipment and the establishment of a Creative Entrepreneurial Corner within the school further supported program sustainability by enabling continuous practice and school-based entrepreneurial activities. Furthermore, participants learned how to package and brand their products while exploring e-commerce platforms to access broader markets. The establishment of a school-based Creative Entrepreneurial Corner under the Scout Group further strengthened program continuity, serving as a platform for ongoing practice and business development. Overall, this initiative demonstrates that integrating digital skills with entrepreneurial training can significantly enhance the self-reliance, creativity, and economic potential of rural youth, offering a replicable model for community development in similar contexts.